Pengaruh Literasi Keuangan, Gaya Hidup dan Pengendalian Diri Terhadap Perilaku Keuangan Generasi Z - Nilamsari, Belgis; Wikartika, Ira (Journal of Business and Economics Research (JBE), 2025)
In this era of globalization, the rapid advancement of technology has had a significant impact on human life. Several factors can influence financial behavior, including financial literacy, lifestyle, and self-control. This study aims to examine the influence of financial literacy, lifestyle, and self-control on the financial behavior of Generation Z in the city of Surabaya. The study population consists of Generation Z individuals residing in Surabaya. A quantitative research method was employed, utilizing primary data collected through questionnaires distributed to Generation Z in Surabaya. The sampling method used was probability sampling with a random sampling technique. Slovin’s formula was applied to determine the sample size, resulting in 100 respondents. The data analysis technique used was SEM-PLS (Partial Least Squares). The results show that financial literacy, lifestyle, and self-control significantly influence the financial behavior of Generation Z in Surabaya, with each variable having a P-value less than α = 0.05, indicating statistical significance. Based on the SEM-PLS analysis, it can be concluded that financial literacy plays an essential role for Generation Z as a fundamental need in effective financial planning. A lifestyle that prioritizes needs over mere wants contributes to healthier financial behavior, and self-control has a strong impact on financial behavior, particularly in financial decision-making.